Feasibility of a CSP Power Plant in Chile under a PPA Model, the Role of Soft Financing and Upfront Grant. (May 2015) - Servert, J.F.; Cerrajero, E.; Fuentealba, E.L.; Greos, S.
Abstract: In Northern Chile, the demand for electricity is expected to grow at a 5% annual rate over the coming years. The primary electricity consumers in the region are mining companies which, due to the characteristics of their activities, have a flat (constant) demand profile. The main energy consumers usually agree(Power Purchase Agreements, PPA) on long-term supply commitments at a fixed price, consistent with stable demand needs. Certain Non-Conventional Renewable Energies (ERNC), such as wind and solar, are or will be competitive to the in Northern Chile, but they do not adapt well to constant demand. CSP technology with thermal energy storage adapts better to the demand profile for Northern Chile but, currently, it isnoncompetitive when compare with a conventional PPA. Financial support, such as soft financing and direct grants, will help narrowing the gap for the first CSP projects in Northern Chile.